CRISPR-Cas9‒Based Genomic Engineering in Keratinocytes: From Technology to Application - Jos P.H. Smits; Luca D. Meesters; Berber G.W. Maste; Huiqing Zhou; Patrick L.J.M. Zeeuwen; Ellen H. van den Bogaard (Elsevier, 2022)
CRISPR-Cas9 is the most straightforward genome-editing tool to date. However, its implementation across disciplines is hampered by variable genome-editing efficiencies, reduced cell viability, and low success rates in obtaining clonal cell lines. This review aims to recognize all CRISPR-Cas9‒related work within the experimental dermatology field to identify key factors for successful strategies in the different keratinocyte (KC) cell sources available. On the basis of these findings, we conclude that most groups use immortalized KCs for generating knockout KCs. Our critical considerations for future studies using CRISPR-Cas9, both for fundamental and clinical applications, may guide implementation strategies of CRISPR-Cas9 technologies in the (experimental) dermatology field.